2021
DOI: 10.1080/01621459.2020.1863221
|View full text |Cite
|
Sign up to set email alerts
|

Minimax Efficient Random Experimental Design Strategies With Application to Model-Robust Design for Prediction

Abstract: In game theory and statistical decision theory, a random (i.e., mixed) decision strategy often outperforms a deterministic strategy in minimax expected loss. As experimental design can be viewed as a game pitting the Statistician against Nature, the use of a random strategy to choose a design will often be beneficial. However, the topic of minimax-efficient random strategies for design selection is mostly unexplored, with consideration limited to Fisherian randomization of the allocation of a predetermined set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…If n mod 3 = 1 then ξ G places (n − 1)/3 observations on each support point and arbitrarily assigns the remaining observation to one of -1, 0 or 1. Waite and Woods (2021) show that a strategy where (n − 1)/3 observations are placed on each support point and the remaining observation is randomly assigned, with probability 1/3, to -1, 0 or 1 outperforms the deterministic approach. Let π G represent the minimax randomized design.…”
Section: Minimax Random Designmentioning
confidence: 98%
See 1 more Smart Citation
“…If n mod 3 = 1 then ξ G places (n − 1)/3 observations on each support point and arbitrarily assigns the remaining observation to one of -1, 0 or 1. Waite and Woods (2021) show that a strategy where (n − 1)/3 observations are placed on each support point and the remaining observation is randomly assigned, with probability 1/3, to -1, 0 or 1 outperforms the deterministic approach. Let π G represent the minimax randomized design.…”
Section: Minimax Random Designmentioning
confidence: 98%
“…factorial, optimal and minimax designs] and designs selected via data independent random processes [e.g. Wu (1981); Li (1983); Waite and Woods (2021)].…”
mentioning
confidence: 99%
“…We will thus for comparison purposes use the same method for our approach, but note that there is no simple way to extend this to higher dimensions. Instead, random sampling according to the measure, according to the random design strategies defined in Waite and Woods (2020), multiple (say 100) times and selecting the sampled design with the best criterion value has in our experience usually led to even more efficient designs.…”
Section: Examplesmentioning
confidence: 99%
“…This seminal paper started a line of work where model misspecification is accounted for in order to compute optimal designs. A review of this body of literature can be found in Wiens (2015); see also the recent work of Waite and Woods (2021). A major theme in this literature is that the bias term is more important than the variance, and therefore one can focus on designs that minimize the bias.…”
Section: Introductionmentioning
confidence: 99%
“…Another important consideration is the randomness of the X's. While it was already mentioned in Wiens (1992) that deterministic designs have infinite minimax risk, random experimental designs were investigated only recently (Waite and Woods, 2021). The latter work shows that random design strategies have smaller minimax error than their deterministic counterparts under linear models.…”
Section: Introductionmentioning
confidence: 99%